Assessing the Neurocognitive Disorders of the Diagnostic and Statistical Manual of Mental Disorders (Fifth Edition). (February 2015) - Crowe, Simon F
<x xml:space="preserve">Abstract</x> The changes to the category of neurocognitive disorders (NCDs) in the Diagnostic and Statistical Manual of Mental Disorders (Fifth Edition) (DSM‐5) include the fact that the diagnoses of both dementia and amnestic disorders are now subsumed under the new category of major NCD. While the term dementia is not precluded from use in the manual, its presence and effect has been significantly reduced. The DSM‐5 also now recognises a less severe form of cognitive impairment, mild NCD, which permits the diagnosis of less disabling presentations of cognitive compromise that may nonetheless be the focus of clinical concern and treatment. Criteria are provided for both of these conditions, each of which is associated with diagnostic criteria for different aetiological subtypes of the disorder. The revised version of the manual represents a significant improvement over the DSM‐IV both in terms of the better description and characterisation of the various clinical entities as well as with regard to the reliability and useability as well as the incorporation of the contemporary science surrounding these conditions.